Inadvertent Disclosure Risk Behind Employee Smartphone Usage - Muhammad Usman Noor (Program Studi Ilmu Perpustakaan, Fakultas Ilmu Budaya, Universitas Diponegoro, 2026)
The leakage of information could lead to material or immaterial losses. Information leakage occurs due to intrusion from outside parties and also due to the negligence of the information owner. Information leakage caused by the information holder referred to as inadvertent disclosure. The impact of inadvertent disclosure is riskier if it occurs in the workplace. In the workplace, confidential and sensitive information or trade secrets cannot be disclosed to the public. In practice, leakage of company information can occur because of tiny, neglected things such as accidentally uploading the information on social media or sending the information to the wrong person on a messaging application, which then brings losses or legal problems. This study uses a quantitative approach with a survey mode of data collection on 220 respondents. The results of this study indicate that most professionals have taken pictures or recorded videos while in the work area or while working; this results in the possibility of confidential information being accidentally recorded. And this confidential issionals access social media and messaging apps more than ten times a day. This phenomenon illustrates that a high frequency of access could increase the risk of inadvertently posting, uploading, or sending wrong photos or videos that contain confidential information that should not be disclosed. The author suggests the need for proper information governance through policy and rules following organizational culture in order to prevent accidental.